Uma aproximação entre a concepção de ser humano de B. F. Skinner e a de Simone de Beauvoir - Romano, Bianca Ferreira (2022)
The objective of this research is to make an approximation between the conception of human being by BF Skinner and Simone de Beauvoir. To achieve this goal, we intend to develop our argument based on the Beauvoirian notion of ambiguity, which expresses the fundamental characteristic of the human being for the philosopher and the crucial point of her thought: the concern with how to articulate a possible individual agency with the limitations of structures social. To do so, first, we draw a brief overview of the development and theoreticalphilosophical foundations of Beauvoir and Skinner. To guide our discussion of the definition of human being for the purposes of this research, we took as dimensions of analysis notions and concepts present in Beauvoir's thought that express the notion of ambiguity as a fundamental characteristic of the Beauvoirian conception of human being: the notion of subjectivity and concepts which fit into it (consciousness, embodiment, intersubjectivity and freedom), the concept of situation, facticity and the notions of historicity and probability; and Skinnerian notions and concepts that more clearly express the author's conception of the human being: Selection by Consequences (its three levels and respective products: organism, person and self), social behavior, verbal behavior and private events, in addition to concept of environment and the notions of historicity and probability